Reliable H∞ control of 2-D continuous nonlinear systems with time varying delays. Issue 12 (December 2015) - Ghous, Imran; Xiang, Zhengrong
Abstract: This paper investigates the reliable H ∞ stabilization problem for a class of two-dimensional (2-D) continuous nonlinear state-delayed systems represented by the Roesser state-space model, where the nonlinear function satisfies the sector bounded condition. By choosing an appropriate Lyapunov–Krasovskii functional, sufficient conditions for asymptotical stability with H ∞ performance of the given system are derived. Then, a reliable controller is proposed such that the resulting closed-loop system is asymptotically stable and has a prescribed H ∞ performance level γ in the presence of actuator failures. Finally, an example is given to illustrate the effectiveness of the proposed method.